Pengaruh Sistem Insentif dan Budaya Organisasi terhadap Kinerja Pegawai di SMKN 20 Samarinda (Jurnal Simki Economic, 2025)
This study aims to analyze the influence of incentive systems and organizational culture on employee performance at SMKN 20 Samarinda. This is rooted in the importance of human resource management in education, where professional and productive employees are the key to achieving organizational goals. At SMKN 20 Samarinda, there are two factors that are considered to be able to influence employee performance, namely incentive systems and organizational culture. The right incentive system is expected to increase work motivation, while a positive organizational culture can create a conducive work environment to support optimal performance. This study uses a quantitative approach with a survey method, where data is collected by distributing questionnaires to 72 employees as respondents. The collected data are analyzed using multiple linear regression to test the relationship between variables. Before the regression analysis is carried out, the validity and reliability of the instrument are tested to ensure the validity of the data. In addition, normality, heteroscedasticity, and multicollinearity tests are carried out to ensure the validity of the regression assumptions. The results of the study indicate that organizational culture has a positive and significant effect on employee performance, while the incentive system does not have a significant effect.